Autism-Risk Gene necab2 Regulates Psychomotor and Social Behavior as a Neuronal Modulator of mGluR1 Signaling - Chen, Zexu; Long, Han; Guo, Jianhua; Wang, Yiran; He, Kezhe; Tao, Chenchen; Li, Xiong; Jiang, Keji; Guo, Su; Pi, Yan (Frontiers in Molecular Neuroscience, 2022)
Background: De novo deletion of the neuronal calcium-binding protein 2 (NECAB2) locus is associated with idiopathic autism spectrum disorders (ASDs). The in vivo function of NECAB2 in the brain remains largely elusive. Methods: We investigated the morphological and behavioral profiles of both necab2 knock-out and overexpression zebrafish models. The expression pattern and molecular role of necab2 were probed through a combination of in vitro and in vivo assays. Results: We show that Necab2 is a neuronal specific, cytoplasmic, and membrane-associated protein, abundantly expressed in the telencephalon, habenula, and cerebellum. Necab2 is distributed peri-synaptically in subsets of glutamatergic and GABAergic neurons. CRISPR/Cas9-generated necab2 knock-out zebrafish display normal morphology but exhibit a decrease in locomotor activity and thigmotaxis with impaired social interaction only in males. Conversely, necab2 overexpression yields behavioral phenotypes opposite to the loss-of-function. Proteomic profiling uncovers a role of Necab2 in modulating signal transduction of G-protein coupled receptors. Specifically, co-immunoprecipitation, immunofluorescence, and confocal live-cell imaging suggest a complex containing NECAB2 and the metabotropic glutamate receptor 1 (mGluR1). In vivo measurement of phosphatidylinositol 4,5-bisphosphate further substantiates that Necab2 promotes mGluR1 signaling. Conclusions: Necab2 regulates psychomotor and social behavior via modulating a signaling cascade downstream of mGluR1.